Diseño y construcción del funcionamiento de un módulo didáctico de subestación de barra simple con transferencia para la visualización de variables eléctricas mediante sistema scada en el laboratorio de electromecánica de la Universidad Técnica de Cotopaxi, periodo 2014 - Jiménez Espinosa, Juan Pablo (2016)
The electrical substation is the set of gadgets and devices processing, conversion and distribution of electricity for feeding an electric power distribution, structure or location outside where the power of a power system is transformed and becomes controls. The construction of the training module of an electrical substation simple transfer bar for displaying electric variables by the SCADA system is intended to deepen the automation and monitoring computer. The study of the functioning of electricity substations was considered important, it is divided as follows: In the first chapter the substation data study and operation of it is presented. The second chapter touches on the actors of the interview in the investigation. The third chapter deals with the development of the proposal, the same details the creation of a sub-station module for electromechanical laboratory at the Technical University of Cotopaxi.